The Influence of Democratic Leadership Style, Motivation and Work Discipline on Employee Performance in the Secretariat of the Kuningan Regency People's Representative Council - Hidayat, Rakes Raditya; Kardiyati, Endah Nurhawaeny (CV. Strata Persada Academia, 2025)
This study examines the influence of democratic leadership style, motivation, and work discipline on the performance of employees at the Secretariat of the Regional People's Representative Council (DPRD) of Kuningan Regency. Conducted over five months using a quantitative approach, data were gathered from all 81 employees via a Likert-scale questionnaire. The results indicate that all three variables significantly influence performance individually and collectively. Motivation emerged as the strongest predictor with a Beta coefficient of 0.658, followed by democratic leadership (0.346) and work discipline (0.330). The F-test confirmed the simultaneous effect of these variables, with an F-statistic of 15.373 and a p-value of 0.000, highlighting their combined impact on employee performance. These findings emphasize the critical role of leadership, motivation, and discipline in enhancing employee outcomes. To improve performance, it is recommended that the Secretariat adopt participative leadership, implement performance-based motivational strategies, and enforce clear disciplinary policies. These measures can foster a supportive work environment, drive organizational success, and enable the Secretariat to effectively fill its administrative and technical support roles.